Prostasin regulates PD-L1 expression in human lung cancer cells. Issue 7 (30th July 2021) - Chen, Li-Mei; Chai, Julius C.; Liu, Bin; Strutt, Tara M.; McKinstry, K. Kai; Chai, Karl X.
Abstract: The serine protease prostasin is a negative regulator of lipopolysaccharide-induced inflammation and has a role in the regulation of cellular immunity. Prostasin expression in cancer cells inhibits migration and metastasis, and reduces epithelial–mesenchymal transition. Programmed death-ligand 1 (PD-L1) is a negative regulator of the immune response and its expression in cancer cells interferes with immune surveillance. The aim of the present study was to investigate if prostasin regulates PD-L1 expression. We established sublines overexpressing various forms of prostasin as well as a subline deficient for the prostasin gene from the Calu-3 human lung cancer cells. We report here that PD-L1 expression induced by interferon-γ (IFNγ) is further enhanced in cells overexpressing the wildtype membrane-anchored prostasin. The PD-L1 protein was localized on the cell surface and released into the culture medium in extracellular vesicles (EVs) with the protease-active prostasin. The epidermal growth factor-epidermal growth factor receptor (EGF-EGFR), protein kinase C (PKC), and mitogen-activated protein kinase (MAPK) participated in the prostasin-mediated up-regulation of PD-L1 expression. A Gene Set Enrichment Analysis (GSEA) of patient lung tumors in The Cancer Genome Atlas (TCGA) database revealed that prostasin and PD-L1 regulate common signaling pathways during tumorigenesis and tumor progression.